Konservasi Lingkungan Melalui Edukasi Zero Waste - Nurhidayah; Mohamad Bastomi (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2023)
The problem that occurs in the community, especially the Jabung sub-district is the increase in plastic waste caused by the use of plastic every day, caring for the environment aims to provide educational information and raise awareness, especially for students of SDN 1 Jabung, by raising awareness of SDN 1 Jabung students will give strength strong aqidah in protecting the environment and awareness of the dangers of excessive plastic use, educational activities are carried out in the form of visualization of material exposure, 3-dimensional media, interactive communication and explanations of various kinds of impacts that have occurred in the surrounding environment. The activity took place in a conducive-mass manner with an audience of 20 students for class VI, class V 15 students and class IV 16 students which resulted in positive feedback in the form of a school environment cleanliness movement and Zero Waste in daily implementation.